PENGARUH KOMPETENSI SUMBER DAYA MANUSIA (SDM), KAPASITAS KERJA KOPERASI, DAN JUMLAH KREDIT TERHADAP KINERJA KEUANGAN KOPERASI - Kharisma Genta, Franklin; Nababan, Daniel (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
In conducting its business, the cooperative requires sufficient capital to support its business as credit unions and business cooperatives.  In Indonesia, the support of the private banking is difficult to obtain because the private banking rarely focuses on the development of cooperatives. Bank Mandiri as a State Owned Enterprises have Mandiri Cooperative Credit Products, under the working units of the Partnership and Community Development (CSR) Bank Mandiri. Programs that are already established as quickly as possible is expected to have a positive effect on cooperatives, in particular on improving its financial performance. This study aims to determine the effect the competence of human resources (HR) (x1), the capacity of cooperative work (x2), and the number of credits (x3) on the financial performance of cooperatives (y) . Indicator used in measuring the financial performance of cooperative seen from the ratio of the activity, liquidity ratios and solvency ratios. The third of the ratio calculation results obtained 56.6% of the 30 samples cooperative has a standard financial ratios under the cooperative health assessment and presumably influence of variable x jointly against the results of the calculation of the variable y. From the results of research using questionnaires given to 30 cooperatives credit recipients and results of a calculation using the software Statistical Package for the Social Sciences (SPSS), indicates that the variable x1 affect the variable y by 87.9%, x2 variables affect the variable y by 68,3%, and variable x3 affect the variable y by 54.5%. Where the variable x1 namely HR competencies possessed great influence on the financial performance of cooperatives.